SYNTHESIS OF CARBON NANOFIBERS AND DIAMOND-LIKE CARBONS BY THE OXYGEN-ACETYLENE TORCH METHOD - Zhumadilov, B.E.; Kenzhegulov, A.K.; Medyanova, B.S.; Ospanali, A.T.; Suyundykova, G.S.; Partizan, G.; Yerlanuly, Ye.; Gabdullin, M.T. (Recent Contributions to Physics, 2022)
This work presents the synthesis of carbon nanofibers and diamond-like carbons by the oxygen-acetylene burner method. Acetylene was used as a carbon source, and metallic films sprayed on silicon substrates were used as a catalyst. The morphological and structural properties of the obtained carbon nanomaterials were studied by scanning electron microscopy and Raman spectroscopy. The influence of the synthesis duration and gas concentration ratio on the structure formation of the deposited samples was studied during the experiments. Diamond-like carbon was synthesized at low gas flow rates and short synthesis times, and carbon nanofibers were obtained when these parameters were increased. The synthesized carbon nanofibers have a cylindrical shape with a diameter of about 50 to 215 nm, and their length reaches several micrometers. The size of diamond-like carbons ranges from 150 to 580 nm. Raman spectroscopy determined that carbon nanofibers have a better degree of ordering and graphitization. According to the results of the studies carried out in this work, the oxygen-acetylene burner can be used as a promising, low-cost alternative for the large-scale production of carbon nanomaterials.